PENGARUH PERBEDAAN KANDUNGAN ASAM LEMAK N-3 DALAM PAKAN TERHADAP PENAMPILAN REPRODUKSI IKAN ZEBRA (Brachydanio rerio) - Nur Bambang Priyo Utomo; Ing Mokoginta; Lia Nurmalia (Jurnal Perikanan Universitas Gadjah Mada, 2006)
This experiment was conducted to determine the dietary n-3 fatty acid requirement for reproduction of broodstock zebrafish, Brachydanio rerio. Three isonitrogenous (39% crude protein) and isocaloric (3,260 kcal digestible energy/kg diet) practical diets, namely diets A, B, and C, with different levels of fatty acids were fed to zebrafish broodstock. The broodstock were cultivated in aquaria. Diet A contained low dosage of n-3 fatty acids (0.4%) and 2% n-6 fatty acids, while diets B and C contained 2% n-6 fatty acids, combined respectively with 1% and 1.5% n-3 fatty acids. Fish were fed ad satiation for 60 days using these diets. During feeding periode, gonade maturation stages were examined. The n-3 and n-6 fatty acids affected fecundity, fertilization rate, and hatching rate. On the other hand, fish fed on diets A, B, or C did not show any significance differences in the gonade somatic index and total Survival Rate (SR) of larvae produced. Fish fed on diet B produced the highest fecundity (616 eggs/g of fish), fertilization rate (94.6%), and hatching rate (93.8%). The total lipid content of eggs were significant, ranging from B (29.7%), C (23.7%), and A (16.1%). At a dosage of 2% n-6 fatty acids, zebrafish require 1% of dietary n-3 fatty acids in the diet for reproduction. Excess dosage of n-3 fatty acid in the diet adversely affected fecundity, fertilization rate, and hatching rate.